A Hospital Based Study on Knowledge and Preventive Practices regarding Dengue Fever among General Patients in Pokhara - Gurung, Gaura; Subedi, Babita; Gharti, Kamala; Thapa, Dharmashila (Journal of Nursing and Health Sciences Nepal, 2025)
Introduction: Dengue fever has become an important public health concern worldwide. In Nepal, recurrent annual outbreaks are reported, and limited awareness about its prevention and management may contribute to increased morbidity and mortality. The spread of dengue is influenced by both human behaviour and environmental conditions. This study aimed to assess the knowledge and preventive practice related to dengue fever among general patients.Methods: A descriptive cross- sectional study was carried out among 185 patients attending the medical outpatient department of Pokhara Academy of Health Science during the data collection period. Data were gathered using an interviewer-administered structured questionnaire to assess respondents’ socio-demographic characteristics, their knowledge of dengue fever and preventive practice. Chi-square tests were used to examine associations between selected socio-demographic factors and knowledge level, while Pearson’s correlation assessed the correlation between knowledge and preventive practices.Results: Of the 185 respondents, 97.8% had heard of dengue fever. The primary sources of information were TV and mobile phones (48.6%). However, only 10.3% demonstrated satisfactory knowledge while 74.1% reported practicing appropriate preventive measures towards dengue fever. Knowledge levels showed a significant association with the respondents’ place of residence, whereas gender, age and educational status were not significantly associated. A significant positive correlation (P